Strategi dan kebijaksanaan P4GN dalam menciptakan penggiat anti Narkoba di lingkungan kerja - Ary Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Drug abuse in Indonesia has reached an alarming level. The largest proportion of drug abusers in 2017 was the group of private workers and laborers, which was 59%. BNNK Batam in collaboration with trade unions and academics conducted a workshop with the theme of strategies and policies on Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) in creating anti-drug activists in the work environment. The purpose of this workshop is so that the participants can become BNN activists in the local environment. The strategies that must be carried out by the company and the trade unions themselves in P4GN's efforts in the work environment include: conducting medical tests for employees; drug testing for employees suspected of being addicts, intensive information dissemination and advocacy to provide education to workers; Trade unions must encourage their members to be active in P2K3, include drug problems in the collective labor agreement (PKB), and for employees: active in spiritual activities, nature lover activities, social activities, in sports activities, trade union activities, adequate rest and relaxation with family on holidays.